Do resources mediate the relationships between the internet and performance in the marketing domain? Testing the role of customer orientation and brand equity. (10th August 2007) - Ordanini, Andrea; Rubera, Gaia
The adoption of internet solutions for marketing increases over time, but a strong empirical evidence of their effect on performance is still lacking. The paper investigates the links existing between the internet, marketing resources and marketing performance, and test a model where two marketing resources ? customer orientation and brand equity ? are expected to mediate the relationship between internet technologies and performance. The analysis, based on a sample of 277 service firms and handled with a structural equation model technique, reveals that a significant partial mediation effect exists for customer orientation but not for brand equity. This effect provides implications for both theory and management.